Evaluation of oxidative DNA damage and antioxidant defense in patients with nasal polyps. (July 2015) - Mrowicka, Malgorzata; Zielinska-Blizniewska, Hanna; Milonski, Jaroslaw; Olszewski, Jurek; Majsterek, Ireneusz
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives The presence of inflammatory cells indicates the development of epithelial cell injury in nasal polyposis (NP) and the potential for production of high levels of reactive oxygen and nitrogen species. The aim of our study was to clarify the role of oxidative stress and antioxidant status in the deterioration accompanying NP. Methods Twenty patients (11 men) aged 47.2 ± 17.0 years with nasal polyps were included in the study. Twenty healthy subjects (7 men) aged 48.2 ± 15.3 years formed the control group. The erythrocyte activities of antioxidant enzymes, superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx), and plasma nitric oxide (NO) concentrations were measured. An alkaline comet assay was used to determine the extent of blood lymphocyte DNA damage of oxidized purines as glicosylo-formamidoglicosylase (Fpg) sites, and oxidized pyrimidines as endonuclease III (Nth) sites. Results A significant increase of NO (P < 0.05) and non-significant decreases of SOD (P > 0.05), CAT (P > 0.05), and GPx (P > 0.05) were seen in NP patients compared to healthy controls. The level of blood lymphocyte oxidative DNA damage in NP patients was significantly higher compared to the control group (P = 0.01). Discussion The blood lymphocyte DNA damage level increased in patients with NP. Elevated DNA damage may be related to overproduction of reactive oxygen and nitrogen species and/or decreased antioxidant protection.